Prognostic and Clinic Pathological Value of Cx43 Expression in Glioma: A Meta-Analysis - Zhang, Chao; Liu, Cheng-fen; Chen, An-bin; Yao, Zhong; Li, Wei-guo; Xu, Shu-jun; Ma, Xiang-yu (Frontiers in Oncology, 2019)
Gap junctional intercellular communication (GJIC) composed of connexin proteins is considered vital to cancer onset and progression since fifty years ago, however altered expression of connexins is still a lesser known ‘hallmark’ of cancer. Although many studies support the hypothesis that connexins are tumor suppressors, recent evidence indicates that, in some tumour types including glioma, they may play contradictory role in some specific stages of tumor progression. We thus conduct a meta-analysis to evaluate the prognostic role of Cx43 in glioma for the unanswered questions. Eight studies with 1706 patients were included for meta-analysis. The results showed that Cx43 expression was a clearly negative factor with tumor grades (I2=34%, P < 0.001) and beneficial for OS (n = 3, HR 2.62, 95%CI 1.47-4.68; P = 0.001). Subgroup analysis also found that Cx43 had different expression in Asian young patients versus other groups. In conclusion, this article summarize the prognostic value of Cx43 and offer a clinical evidence for the notion that Cx43 is generally a tumor suppressor and beneficial for the patients’ survival time.